The Influence of the PQ4R Learning Method Assisted by Balinese Folk Story Texts on Elementary School Student Reading Comprehension Ability - Primayana, Kadek Hengki; Dewi, Putu Yulia Angga (Universitas Pendidikan Ganesha, 2025)
Elementary school students' reading comprehension skills are still relatively low, partly due to the limited variety of teaching methods used and the suboptimal integration of local content as learning media. This condition highlights the need for instructional strategies that can enhance student engagement and provide more meaningful understanding. This study aims to analyze the effect of the PQ4R learning method supported by Balinese folklore texts on the reading comprehension abilities of fourth-grade elementary school students. A quasi-experimental method was used to measure the effectiveness of the PQ4R learning model on reading comprehension skills. The sample consisted of 36 fourth-grade students. Based on the results obtained through a t-test using the SPSS program, a significance value (Sig) of 0.000 was obtained, which is smaller than the significance level of 0.05, indicating that Ho is rejected and Ha is accepted. Therefore, it can be concluded that there is a significant influence on reading comprehension ability between the group taught using the PQ4R method assisted by Balinese folklore texts and the group taught using conventional instruction. The implication of this research suggests that integrating the PQ4R method with Balinese folklore texts can serve as an effective alternative teaching strategy to improve students' reading comprehension while also supporting the preservation of local cultural values in the learning process.